Pengembangan Sarana dan prasarana Pendukung Pembelajaran Studi Kasus SMK Ibnu Sina: Development of Facilities and Infrastructure to Support Learning Case Study of Ibnu Sina Vocational High School - Nofri Yudi Arifin (Engineering and Technology International Journal, 2021)
The success of educational programs in the teaching and learning process is strongly influenced by several factors, such as students, curriculum, educators and educational agents, funds, facilities and infrastructure as well as environmental factors. One of the factors that support the success of educational programs in the learning process is educational facilities and infrastructure. This study aims to design a system that can assist in the management of facilities and infrastructure at the vocational high school of SMK Ibnu Sina Batam, in an effort to improve the performance of the management of school facilities and infrastructure that supports learning and practicum. implement a system that can assist education officers in managing data on existing facilities and infrastructure, and can more quickly gain profits and changes in improving the quality of education at Ibnu Sina Junior High School Batam in the future.